Effects of recycled concrete aggregate on the fresh properties of self-consolidating concrete - Safiuddin, M.D.; Salam, M.A.; Jumaat, Mohd Zamin (Archives of Civil and Mechanical Engineering, 2011)
Concrete wastes are generally delivered to the landfill sites for disposal. Due to increasing charges of landfill and scarcity of natural coarse aggregate (NCA), recycled concrete aggregate (RCA) derived from concrete wastes is growing interest in construction industry. In the present study, RCA was used as partial and full re-placements of NCA to produce self-consolidating concrete (SCC). Different SCC mixes were produced with RCA substituting 0, 30, 50, 70, and 100 NCA by weight. The water to cement (W/C) ratio and high-range water reducer (HRWR) dosage were kept the same for all concretes. The effects of RCA on the key fresh properties such as filling ability, passing ability, and segregation resistance of SCC were investigated. The test results revealed that the filling ability and passing ability of SCC were improved for 30 and 50 RCA. The SCC mixes with 30 and 50 RCA also possessed adequate segregation resistance. In addition, strong correla-tions were observed for filling ability, passing ability, and segregation resistance. The overall test results suggest that RCA can be used to produce SCC substituting up to 50 NCA without affecting the key fresh properties of concrete.